Researching war feminist methods, ethics and politics - Wibben, Annick T. R. (Routledge, Taylor & Francis Group, 2016)
Researching War provides a unique overview of varied feminist contributions to the study of war through case studies from around the world. This book: Provides a multi-disciplinary perspective on war by drawing on disciplines such as anthropology, history, literature, peace research, postcolonial theory, queer studies, security studies, and women's studies; Showcases a multiplicity of experiences with war and violence, emphasizing everyday experiences of war and violence with accounts from around the world.